Gross Domestic Product and Labour Force Development Tendencies in the Baltic States, 2000 - 2011 - Ulnicāns, Einārs (Lithuanian Journal of Statistics, 2012)
The article with calculations analyses the development tendencies of gross domestic product, employment,unemployment, labour productivity and loss of unemployment in the Baltic States during 2000 - 2011. The results of thecalculations are explained in the description of these trends and their obvious and possible causes. A brief concept of thetheoretical background and the main formula for the calculation of labour productivity is provided as well. Conclusions aredrawn about the overall character of the development trends. The overall trends of economic development are similar in allthree countries. Gross domestic product, employment and labour productivity were growing until 2007. From 2008 to 2010they fell as a result of the economic crisis, but in 2011 all the indicators began rising again. Major changes in movement,including negative changes, are more frequently observed in Lithuania and Estonia. Differences between the countries appearin nuances, especially in Lithuania.
Keywords: Gross domestic product; employed persons; unemployed persons; labour productivity; loss of unemployment; Baltic States